Bryobia abyssiniae (Prostigmata: Tetranychidae), a new species from the highlands of Ethiopia. Issue 7 (2nd October 2016) - Fashing, Norman J.; Ueckermann, Edward A.; Fashing, Peter J.; Nguyen, Nga; Back, Amanda M.; Allison, Lizabeth A.
ABSTRACT: Bryobia abyssiniae Fashing & Ueckermann, a recently discovered species, is described using DNA-barcoding as well as morphological features of the adult female and all post-embryonic instars. The species is characterized by remarkable propodosomal lobe variation. A lack of variation in molecular markers indicates that the several forms observed reflect intraspecific variability in this apparently all-female species. Its host plant, a giant lobelia ( Lobelia rhynchopetalum Hemsl.; Campanulaceae), is endemic to the Ethiopian highlands. A discussion of climate at the collection locality, the host plant, and notes on biology are also included. Additionally, we suggest that a minimum of 5% sequence difference in the mitochondrialcytochrome c oxidase subunit I region will be needed to differentiate Bryobia species.